Horns [videorecording (DVD)] - Radcliffe, Daniel, 1989-; Temple, Juno, 1989-; Minghella, Max, 1985-; Hill, Joe (Starz Media, 2015)
A supernatural thriller driven by fantasy, mystery, and romance follows Ig Perrish, the number one suspect in the murder of his girlfriend, Merrin. Hung over from a night of hard drinking, Ig awakens one morning to find horns growing from his head and soon realizes their power drives people to confess their sins and give in to their most selfish and unspeakable impulses - an effective tool in his quest to discover what happened to his girlfriend and exact revenge on her killer.